COPING STRESS PADA WANITA PASCA EKLAMPSIA - Tanihatu, Genevieva Esmeraldine; Sipasulta, Grace Carol (PAMERI, 2023)
One of the most important stages in a woman's life involves pregnancy, birth and motherhood. Every woman experiences a unique period of pregnancy, and each individual reacts to it in a different way. Because of this, pregnancy is considered a critical period in a woman's life. Pregnancy also brings about major changes that may be unfamiliar to women. One example is Eclampsia, which can cause anxiety in pregnant women even after the period has passed. Although it is sometimes difficult to assert, the discomfort of anxiety is always felt. For this reason, a problem-solving strategy is needed or commonly called a coping strategy that aims to reduce, or minimize a stressful situation or event with various mental and behavioral efforts to overcome the feelings of anxiety faced by the mother. Qualitative method with a case study approach to the subject with a deep interview. The results obtained are in eclampsia cases, the Stress Coping approach is more useful in handling it. The Stress Coping Strategy used is more often with an emotionally focused approach.